1981
DOI: 10.1111/j.1348-0421.1981.tb00045.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Effect of Beta Toxin of Clostridium perfringens Type C on Rats

Abstract: The biological effect of purified beta toxin of Clostridium perfringens type C in vivo was investigated. After intravenous injection of the purified beta toxin into rats, a rise in blood pressure and a simultaneous fall in heart rate were observed. After the blood pressure reached a maximum, the heart rate recovered gradually, and electrocardiographic and respiratory changes began. The rise in blood pressure induced by beta toxin tended to be proportional to the amount of toxin. The latent period between the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
2

Year Published

1984
1984
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 10 publications
1
22
0
2
Order By: Relevance
“…To study the mode of action of the toxin, it is important to determine the pharmaco logicaleffect of the purified toxin in vivo. We reported that the purified toxin causes a rise in arterial blood pressure, and that alpha blocking agents such as phen tolamineand phenoxybenzamine lower or inhibit the hypertension induced by the injection of beta toxin (21). The present study gives further evidence for the pressor response to the toxin.…”
supporting
confidence: 62%
See 2 more Smart Citations
“…To study the mode of action of the toxin, it is important to determine the pharmaco logicaleffect of the purified toxin in vivo. We reported that the purified toxin causes a rise in arterial blood pressure, and that alpha blocking agents such as phen tolamineand phenoxybenzamine lower or inhibit the hypertension induced by the injection of beta toxin (21). The present study gives further evidence for the pressor response to the toxin.…”
supporting
confidence: 62%
“…The present study shows that treatment with blockers acting on the auto nomicnervous system and removal of the adrenal medulla or spinal cord significantly inhibit the elevation in blood pressure induced by beta toxin of Clostridium perfringens type C. Previously we reported that the pharmacological effects of beta toxin on the cardiovascular system of rats include pressor responses (the elevations in systolic and diastolic pressure), bradycardia and arrhythmia and that alpha blocking agents prevent the elevation elicited by the toxin (21). The toxin-induced rise in pressure was accompanied by an increase in blood glucose (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, these toxins, enterotoxin and delta toxin, may possibly perform some roles in the enteritis necroticans of man and animals as well as beta toxin. The purification and biological characterization of ILEAL LOOP RESPONSE TO C. PERFRINGENS 867 beta and delta toxins have already been reported (1,14), but the response of ligated rabbit ileal loops to these purified toxins has not been observed. Further experiments on the response of ligated loops to these purified toxins are in progress at our laboratory.…”
Section: Response Of Ligated Rabbit Ileal Loop To Toxic Filtrate Of Cmentioning
confidence: 99%
“…Είναι η δεύτερη πιο θανατηφόρα τοξίνη του C perfringens, μετά την τοξίνη -ε. Η διαδικασία σύνδεσης της με τους υποδοχείς είναι μη αντιστρέψιμη, με απο τέλεσμα η χορήγηση αντιορού μετά τη σύνδεση να μην μπορεί να εξουδετερώσει την τοξίνη (Sakurai et al 1981). Ασκεί την παθογόνο της δράση σχηματί ζοντας πόρους με ολιγομερισμό της κυτταρικής μεμ βράνης.…”
Section: τοξίνη -βunclassified